Patient‐reported outcomes after Tixagevimab and Cilgavimab pre‐exposure prophylaxis among solid organ transplant recipients: Safety, effectiveness, and perceptions of risk. Issue 4 (1st February 2023) - Alejo, Jennifer L.; Kim, Jake D.; Chiang, Teresa P.Y.; Avery, Robin K.; Karaba, Andrew H.; Jefferis, Alexa; Warren, Daniel S.; Massie, Allan B.; Tobian, Aaron A.R.; Segev, Dorry L.; Werbel, William A.
Abstract: Background: Tixagevimab and Cilgavimab (T + C) is authorized for pre‐exposure prophylaxis (PrEP) against Coronavirus Disease 2019 (COVID‐19) in solid organ transplant recipients (SOTRs), yet patient‐reported outcomes after injection are not well described. Furthermore, changes in risk tolerance after T + C PrEP have not been reported, of interest given uncertain activity against emerging Omicron sublineages. Methods: Within a national prospective observational study, SOTRs who reported receiving T + C were surveyed for 3 months to ascertain: (1) local and systemic reactogenicity, (2) severe adverse events with focus on cardiovascular and alloimmune complications, and (3) breakthrough COVID‐19, contextualized through (4) changes in attitudes regarding COVID‐19 risk and behaviors. Results: At 7 days postinjection, the most common reactions were mild fatigue (29%), headache (20%), and pain at injection sites (18%). Severe adverse events were uncommon; over 3 months of follow‐up, 4/392 (1%) reported acute rejection and one (.3%) reported a myocardial infarction. Breakthrough COVID‐19 occurred in 9%, 16–129 days after receiving full dose (300/300 mg) T + C, including two non‐ICU hospitalizations. Most surveyed SOTRs (65%) felt T + C PrEP was likely to reduce their COVID‐19 risk, and 70% reported increased willingness to engage in social activities such as visiting friends. However, few felt safe to return to in‐person work (20%) or cease public mask‐wearing (15%). Conclusions: In this prospective study of patient‐reported outcomes, T + C was well tolerated with few serious events. Several COVID‐19 breakthroughs were reported, notable as most SOTRs reported changes in risk tolerance after T + C. These results aid counseling of SOTRs regarding real‐world safety and effectiveness of T + C.